Theabrownin triggers DNA damage to suppress human osteosarcoma U2OS cells by activating p53 signalling pathway. Issue 9 (11th July 2018) - Jin, Wangdong; Zhou, Li; Yan, Bo; Yan, Li; Liu, Fucun; Tong, Peijian; Yu, Wenhua; Dong, Xiaoqiao; Xie, Li; Zhang, Jin; Xu, Yiqiao; Li, Chunqi; et al.
Abstract: Osteosarcoma becomes the second leading cause of cancer death in the younger population. Current outcomes of chemotherapy on osteosarcoma were unsatisfactory to date, demanding development of effective therapies. Tea is a commonly used beverage beneficial to human health. As a major component of tea, theabrownin has been reported to possess anti‐cancer activity. To evaluate its anti‐osteosarcoma effect, we established a xenograft model of zebrafish and employed U2OS cells for in vivo and in vitro assays. The animal data showed that TB significantly inhibited the tumour growth with stronger effect than that of chemotherapy. The cellular data confirmed that TB‐triggered DNA damage and induced apoptosis of U2OS cells by regulation of Mki67, PARP, caspase 3 and H2AX, and Western blot assay showed an activation of p53 signalling pathway. When P53 was knocked down by siRNA, the subsequent downstream signalling was blocked, indicating a p53‐dependent mechanism of TB on U2OS cells (p53 wt). Using osteosarcoma cell lines with p53 mutations (HOS, SAOS‐2 and MG63), we found that TB exerted stronger inhibitory effect on U2OS cells than that on p53‐mut cell lines, but it also exerted obvious effect on SAOS‐2 cells (p53 null), suggesting an activation of p53‐independent pathway in the p53‐null cells. Interestingly, theabrownin was found to have no toxicity on normal tissue in vivo and could even increase the viability of p53‐wt normal cells. In sum, theabrownin could trigger DNA damage and induce apoptosis on U2OS cells via a p53‐dependent mechanism, being a promising candidate for osteosarcoma therapy.